2015
DOI: 10.1016/j.chiabu.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Children's experiences of companion animal maltreatment in households characterized by intimate partner violence

Abstract: Cruelty toward companion animals is a well-documented, coercive tactic used by abusive partners to intimidate and control their intimate partners. Experiences of co-occurring violence are common for children living in families with intimate partner violence (IPV) and surveys show that more than half are also exposed to abuse of their pets. Given children’s relationships with their pets, witnessing such abuse may be traumatic for them. Yet little is known about the prevalence and significance of this issue for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 55 publications
(68 reference statements)
7
65
0
1
Order By: Relevance
“…That is, women in our study recounted pets being mistreated by threats to kill or harm, and kicking, punching, strangling, and the use of guns and other weapons. The theme of children’s proximity to animal maltreatment is consistent with prior qualitative research on children’s self-reports of exposure to animal maltreatment, which has documented children’s direct exposure to animal maltreatment in the context of violent interparental conflict as well as incidents when animals are harshly punished for undesired behaviors (McDonald et al, 2015). It is important to note that directly witnessing (seeing) interparental violence puts children at greater risk of compromised developmental outcomes than indirect exposure such as being told about violent acts or seeing the affective or environmental aftereffects of violence (Hamby et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…That is, women in our study recounted pets being mistreated by threats to kill or harm, and kicking, punching, strangling, and the use of guns and other weapons. The theme of children’s proximity to animal maltreatment is consistent with prior qualitative research on children’s self-reports of exposure to animal maltreatment, which has documented children’s direct exposure to animal maltreatment in the context of violent interparental conflict as well as incidents when animals are harshly punished for undesired behaviors (McDonald et al, 2015). It is important to note that directly witnessing (seeing) interparental violence puts children at greater risk of compromised developmental outcomes than indirect exposure such as being told about violent acts or seeing the affective or environmental aftereffects of violence (Hamby et al, 2011).…”
Section: Discussionsupporting
confidence: 76%
“…In high-stress, unpredictable environments such as households experiencing family violence, exposure to animal abuse may be particularly traumatic for children for whom pets serve as security-providing attachment figures (McDonald et al, 2015; Melson, 2003; Yorke, 2010). Moreover, recent qualitative research suggests that violence in families where animal maltreatment is present is multidirectional and children’s exposure to animal maltreatment is often complex, involving violence at the hands of multiple family members with multifarious motives (McDonald et al, 2015). Reporting on qualitative interview data from 58 school-aged (7–12 years) children recruited from residential and nonresidential DV services, McDonald et al (2015) found three themes across children’s accounts of their exposure to animal maltreatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study about the impact of domestic violence on children, McDonald et al [9] studied the co-occurrence of animal abuse and domestic violence. The authors found several different common scenarios, including a perpetrator hurting an animal to punish their adult partner, an animal getting caught in the middle of an episode of violence, a sibling injuring a pet, and children intervening to prevent pet abuse or to protect a pet caught up in the middle of violence.…”
Section: Emotional Abuse and Intimate Partner Violencementioning
confidence: 99%